Ibrutinib in Refractory or Relapsing Primary Central Nervous System Lymphoma: A Systematic Review - Gaurav Nepal; Mahika Khurana; Domenica Herrera Bucheli; Siddhartha Bhandari; Utsav Joshi; Riwaj Bhagat; Jessica Holly Rehrig; Prasun Pudasainee; Yow Ka Shing; Juan Fernando Ortiz; Rajeev Ojha; Bikram Prasad Gajurel; et al. (MDPI AG, 2022)
Primary Central Nervous System Lymphoma (PCNSL) is a rare variant of Non-Hodgkin Lymphoma (NHL) representing 1-2% of all NHL cases. PCNSL is defined as a lymphoma that occurs in the brain, spinal cord, leptomeninges, or eyes. Efforts to treat PCNSL by traditional chemotherapy and radiotherapy have generally been unsuccessful as a significant proportion of patients have frequent relapses or are refractory to treatment. The prognosis of patients with Refractory or Relapsed (R/R) PCNSL is abysmal. The optimal treatment for R/R PCNSL is poorly defined as there are only a limited number of studies in this setting. Several studies have recently shown that ibrutinib, a Bruton tyrosine kinase (BTK) inhibitor, has promising results in the treatment of R/R PCNSL. However, these are preliminary studies with a limited sample size. In this systematic review, we explored and critically appraised the evidence about the efficacy of the novel agent ibrutinib in treating R/R PCNSL.